The Governance of Public Policy Evaluation Systems: Policy Effectiveness and Accountability - Filgueiras, Fernando; de Fátima Nascimento Queiroz, Lúcia (Organizações & Sociedade, 2021)
Do different institutional arrangements of public policy evaluation systems produce different results in promoting accountability and government effectiveness? Our study aims at discussing the governance of public policy evaluation systems. For such purpose, the evaluation systems of Canada, Chile, France, Mexico, Spain, Sweden, the United Kingdom, and the United States were analyzed using the QCA methodology. Our analysis seeks to evaluate the institutional arrangements for the governance of evaluation systems and the conditions necessary and sufficient for them to promote greater governmental effectiveness and accountability. In conclusion, the process of delegating power to evaluation systems should include the involvement of the Legislative Branch to ensure that they help increase governmental effectiveness and promote accountability.